Informal, formal, or both? Assessing the drivers of home care utilization in Austria using a simultaneous decision framework - Matthias Firgo; Klaus Nowotny; Alexander Braun (Austrian Institute of Economic Research (WIFO), 2017)
Understanding the relation between different types of long-term care and the determinants of individual choice of long-term care types is fundamental for efficient policy making in times of ageing societies. However, empirical research on this issue has revealed both national and methodological factors as crucial for the policy conclusions drawn. Thus, the purpose of the present paper is twofold: First, at least to our knowledge, it is the first comprehensive assessment of this kind for Austria. Second, it extends the scarce literature explicitly focusing on the combined use of informal and formal care in addition to the exclusive use of these services based on an econometric framework accounting for the simultaneity and interdependencies in these types of long-term care. Our results provide strong evidence for a taskspecific and complementary relation of formal and informal home care in Austria, with the health status and functional limitations as the main determinants of individual choice.
Keywords: C35; H44; I11; I12; J14; 330; long-term care; formal; informal; bivariate probit; SHARE; Austria